Phlebitis, Infiltration, and Localized Site Infection Among Patients With Peripheral Intravenous Catheters - Gargar, Alvin P.; Cutamora, Jezyl C.; Abocejo, Ferdinand T. (European Scientific Journal, ESJ, 2017)
This study examined the occurrence of phlebitis, infiltration, and localized site infection between standard replacement (control group) and clinically indicated replacement (experimental group) among patients with peripheral IV catheters. We utilized a two-group, post-test only, randomized experimental design in a level 4 tertiary hospital in Cebu for a period of 30 days. A total of 80 participants who passed the selection criteria were chosen and equally divided into 2 groups of 40 members each using randomization. The control group had their peripheral IV catheters changed every 3 days while the experimental group had their peripheral IV catheters replaced only in the presence of complications. The outcome variables for the study were phlebitis, infiltration, and localized site infection. Findings revealed that the standard replacement group had a higher prevalence rate of complications compared to the clinically indicated replacement group. Moreover, patients who stayed for 7-14 days had an increased likelihood of developing phlebitis and infiltration compared to those who remained for 4-6 days. Remarkably, peripheral IV catheters inserted by physicians had a higher rate of infiltration compared to nurses. Furthermore, nurses who had 2 years of experience were found to have lower incidence of phlebitis compared to those who had 3 years of experience. In conclusion, the risk of developing phlebitis and infiltration was not increased when peripheral IV catheters were replaced on a clinical-need rather than on a routine basis. Hospitals should consider adopting new guidelines wherein peripheral IV catheters are changed only in the presence of complications.